Tradisi Bapalas Bidan Pada Masyarakat Suku Dayak Menurut Mazhab Syafi’i - Rahmawati Rahmawati; Hallymah Thussadyah Maura Putri; Anwar Hafidzi (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2023)
Dayak tribes are often known to people with various traditions. One of the customs that are still preserved is the tradition of Bapalas Bidan. Bapalas Bidan is a mother's gratitude to God for giving birth to a safe and healthy child and a thank you to the midwife who served her, from the womb to the birth of the baby and until the umbilical cord broke. The tradition of bapalas bidan has several stages, the process includes: first bathing the baby, second set foot to the ground, third ritual meayun bayi (swinging baby), fourth ritual batapung tawar and salvation. The research method used in this study is a qualitative research method that is processed by descriptive analysis approach. The Data obtained through interviews with Dayak people who experience or perform the tradition of Bapalas Bidan and from literature studies, namely books, theses and journals which will then be correlated with the views of the Shafi'i school. The results of this study is that the tradition of Bapalas midwives for them Dayak tribe is possible. Meanwhile, according to the Shafi'i school, this tardisi should not be done because it contains shirk which is categorized as ‘urf fasid. However, if the implementation does not contain elements of shirk or signed with the Shari'a, this tradition is categorized as ‘urf Saheeh and the Shafi'i school allows ' ur Saheeh as evidence for the tradition of Bapalas Bidan. This tradition aims as a form of gratitude to God for having been blessed with a healthy and safe child and as a form of appreciation to midwives who have helped all the pregnancy process until delivery. And as a form of preservation of customs that have prevailed since ancient times.